2021
DOI: 10.1080/19475705.2021.1890235
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal shifts in thermal climate in responses to urban cover changes: a-case analysis of major cities in Punjab, Pakistan

Abstract: This study investigates the relationship of urban thermal environment (UTE) with various influential factors as well as ecological conditions. The relation between LST and land use and land cover (LULC) changes was explored in terms of remote-sensing (RS) based indices; heat effect contribution index (HECI), Urban thermal field variance index (UTFVI), Surface urban heat island intensity (SUHII), Normal Difference Built-up Index (NDBI), and Normal Difference Vegetation Index (NDVI). LULC maps were classified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 84 publications
(94 reference statements)
2
9
0
Order By: Relevance
“…The inner-city areas became congested due to the low availability of land for new development, resulting in other environmental and social issues. The LST for each category of LULC was also evaluated in this study, and it was observed that barren land and built-up area have the highest LST and similar results have been observed in other six urban centers in Pakistan (Dilawar et al, 2021). The mean, maximum, and minimum LST of all categories of LULC recorded a consistent increase, and a similar increase was also observed in other studies (Ibrahim and Rasul, 2017;Dilawar et al, 2021;Moazzam et al, 2022).…”
Section: Figuresupporting
confidence: 83%
“…The inner-city areas became congested due to the low availability of land for new development, resulting in other environmental and social issues. The LST for each category of LULC was also evaluated in this study, and it was observed that barren land and built-up area have the highest LST and similar results have been observed in other six urban centers in Pakistan (Dilawar et al, 2021). The mean, maximum, and minimum LST of all categories of LULC recorded a consistent increase, and a similar increase was also observed in other studies (Ibrahim and Rasul, 2017;Dilawar et al, 2021;Moazzam et al, 2022).…”
Section: Figuresupporting
confidence: 83%
“…An important feature observed concerning LULC changes in Karachi during 2000-2020 was that the cropland and open bare land were first converted into areas of open land before becoming part of the built-up area. This type of change pattern was also observed in high-density metropolitan cities, such as Hyderabad [33] and Faisalabad [66]. This process was due to the fact that agricultural land and other types of land acquired by real estate companies were left open for many years before being rebuilt or restructured.…”
Section: Discussionmentioning
confidence: 64%
“…The subject of how urbanization affects groundwater depletion has received extensive attention [7]. The urban expansion of human settlements and industrial development has affected urban growth patterns, resulting in the conversion of many fertile land surfaces into built-up regions [8]. Many business organizations and enterprises in various regions of the world use groundwater as well, especially for industries, such as paper, marble cutting, food, beverages, and other materials [9].…”
Section: Introductionmentioning
confidence: 99%